Public Private Partnership in Redevelopment of Railway Stations Model Concession Agreement - Planning Commission (Planning Commission, 2014)
The Railways constitute the backbone of transportation infrastructure and provide an economic and environment friendly option compared to other modes of land transportation. The Indian Railways have a network of over 63,000 km that carries 17 million passengers and 2 million tonnes of freight traffic every day. Given the competing demands for capacity addition, the Railways are usually short of resources for the upkeep and renovation of their assets such as the Railway Stations, most of which were constructed several decades ago. The Railways have, therefore, decided to invite private participation for modernising 26 stations to world-class standards. Public Private Partnerships (PPPs) have the added advantage that they lend themselves to a clear specification of levels of service quality based on benchmarks that have been achieved elsewhere.
Planning Commission Government of India
Planning Commission Government of India